Praktik sosial Gaya Hidup Nawaning (Putri Kyai) di Pesantren Berbasis Salaf di Era Globalisasi - Kholida Ulfi Mubaroka (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This articles is the result of the research on the social practice contradiction of nawaning or Kiai’s daughter in the salaf Islamic Boarding School in the globalization era. This research explains how social practices of nawaning in the salaf Islamic Boarding School in the globalization era is. The research explains how the process is carried out and then produces social behaviors that exist in the environment. The theory used in this research is the theory of Anthony Gidden. This theory describe the era of globalization as 'uncontrolled world'. In addition, it also uses Bourdieu's theory as a supporting theory in the analysis. This study uses a qualitative method that departs from a data to analyze a particular problem. Data collection in this study was carried out by observing techniques that are observing the Islamic Boarding School environment, the participation of researchers involved in nawaning activities in Islamic Boarding School, interview, and literature study. The results of this study indicate that the social practice of nawaning in the Salaf Islamic Boarding School has a contradictory nature in the Islamic Boarding School environment. Nawaning behavior by using owned capital as a form of class domination in the environment. Then in practice they try to produce language to offer new values in the environment of the Salaf boarding school. There is dialectic between nawaning actors and also the actors under it namely santri. So that the social practices adopted by these nawaning are contradictory to the rules and values that apply in the Salaf Islamic Boarding School.